Mass neutrino flavor evolution in spacetime with torsion - Zhang, C. M. (Editrice Compositori Bologna, 2000)
In the framework of the spacetime with torsion, we obtain the flavor evolution equation of the mass neutrino oscillation in vacuum. A comparison with the result of general relativity case shows that the flavor evolutionary equations in Riemann spacetime and Weitzenbock spacetimes are equivalent in the spherical symmetric Schwarzschild spacetime, but turn out to be different in the case of the axial symmetry.